Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:FQKKVE4W 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgnd3 previousDOI: 10.5281/zenodo.3903213 shortDOI: 10/ghgnd3 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3903213 10.5281/zenodo.3903213 10.53832/edtechhub.0038 10/ghgnd3 2339240:4GMNADXW 2339240:NJVI79X2 2339240:VJKBU72Y 2405685:C5MWWQI2 2405685:D25NXEFY 2405685:NNCCIL5M 2405685:RHJ9EDQH 4656463:K7AIYRDP
Keywords: C:Sierra Leone; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Education service transformation in Sierra Leone: Where policy meets the people | Blog | Global Partnership for Education - Sengeh, David Moinina (2020)
As GPE prepares to launch a new five-year strategic plan responding to partner countries’ demands for transformative change, GPE Board Member and Minister of Basic and Senior Secondary Education David Moinina Sengeh shares learnings from his first year of office on what transforming education means to the people of Sierra Leone.
KerkoCite.ItemAlsoKnownAs: 2339240:DE8NBSA7 2405685:TJT9ZI8V

Leh Wi Lan: Improving The Quality Of Secondary Education In Sierra Leone - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:Y7RFFB9I

Transforming education service delivery in Sierra Leone: from evidence to action - Sengeh, David Moinina; May-Wilson, Hannah (Global Partnership for Education, 2020)
Sierra Leone’s education system has been plagued by events that have challenged the effective delivery of high-quality education for every child for nearly three decades. But thanks to a program launched in 2018, the government is achieving greater access, quality, and equity for children by removing financial barriers to school enrollment and improving teaching and learning outcomes.
KerkoCite.ItemAlsoKnownAs: 2339240:BFQBRATB 2405685:PS758V8V

Worldreader | Sierra Leone - Worldreader (2020)
Worldreader brings digital reading to schools in Sierra Leone in partnership with the Klintworth Family Foundation.
Library Catalog: www.worldreader.org EdTechHub.ItemAlsoKnownAs: 2405685:FHAMLZRG

Government–donor relations in Sierra Leone: Who is in the driving seat? - Harris, David; Conteh, Felix Marco (The Journal of Modern African Studies, 2020)
Since the cessation of conflict in 2002, Sierra Leone has experienced extraordinary levels of involvement from Western donors. Paradoxically, while relationships are often portrayed on the ground as strong with significant donor influence, our research shows considerable fluidity in individual and institutional relationships. The article disaggregates donor–government relations at various levels over a short but crucial period, 2010–16, asking in each case who occupies the driving seat. In so doing, the article interrogates the concept of ‘extraversion’, investigating to what extent government – and indeed donors – has space in which to manoeuvre and how and why government and donors act as they do in this space. The period 2010–16 is of particular interest due to extreme iron ore price volatility and the Ebola epidemic of 2014–15. The article adds much-needed critique and empirical evidence to the debate on donor influence and ‘extraversion’.
KerkoCite.ItemAlsoKnownAs: 10.1017/S0022278X19000569 2339240:6BGFKPNW 2405685:ZJ7VE4Y6

Sierra Leone Demographic and Health Survey 2019 - Statistics Sierra Leone (The DHS Program, 2020)
ICF
KerkoCite.ItemAlsoKnownAs: 2339240:J5MWI9UW 2405685:MEUW6R9C 2405685:MZXSNEV5

Orange Education Portal - Orange Sierra Leone (2020)
Library Catalog: www.orange.sl KerkoCite.ItemAlsoKnownAs: 2405685:YV3WDQAQ

Universal Access Development Fund | Home - Universal Access Development Fund (Sierra Leone) (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:FNIEIP9B

Schools ICT project - Universal Access Development Fund (Sierra Leone) (2020)
Library Catalog: uadf.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:UXGCRKTI

Scientists at DSTI go the extra mile to make it easier for children to get to school - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
Mike Fabrikant, a software developer from Washington D.C., is embedded within the data science team at the Directorate of Science, Technology, and Innovation (DSTI) to support systems delivery. His workRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:9K5VWY7C

DSTI | Home - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T64PHUNV

Ministry of Information and Communications | Home - Ministry of Information and Communications (Sierra Leone) (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:MV5RWXEF

EMIS | Education Management Information System - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
Library Catalog: mbsse.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:WDHKTX4J

COVID-19 Education Emergency Response Plan - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:XV46GE39

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707884 2339240:6XDHWICN 2405685:7FQR6GZK 2405685:Y22H6PQD
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and students could access and use…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707888 2405685:E2KWWHCK 2405685:LND4UENT
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko - SN Radio (2020)
#sierraleone #presidentbio #fatimabio #sierraleoneparliament #sierranetworkproduction #sierranetwork #sierranetworkwanpotshow President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko. Latest News Website: http://www.blog.snradio.net FaceBook: http://www.facebook.com/SierraNetwork... Youtube: http://www.youtube.com/Salone2Bad Twitter: http://twitter.com/sierra_n_salone Radio: http://SNRadio.net Radio TuneIn App: http://tun.in/sfgyD SoundCould 1: http://www.soundcloud.com/sierra-network SoundCould 2: https://soundcloud.com/sierra-network-sl SoundCould 3: https://soundcloud.com/sierra-network... Contact Us: info@snradio.net Sierra Network For All That Matters Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2405685:PZEXZU6E

Mitigating COVID-19 impacts and getting education systems up and running again: Lessons from Sierra Leone - Davis, Edward; Berry, Chris (Global Partnership for Education, 2020)
Reflexions on some of the lessons from the Sierra Leone Ebola education response that could be relevant for countries facing shutdowns of their education systems due to the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:NIUY9YWK 2405685:CVJKIQ8D

RECOVR Sierra Leone: Tracking the Effects of the COVID-19 Pandemic - Warren, Shana; Parkerson, Doug; Collins, Elliott (Innovations for Poverty Action, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:BU58QF73

Education service transformation in Sierra Leone: Where policy meets the people - Sengeh, David (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Y5AL4GBH 2405685:CL5T3HVF

Sierra Leone | Education and Literacy Statistics - UNESCO (2020)
...
Last Modified: 2017-04-12 Library Catalog: uis.unesco.org KerkoCite.ItemAlsoKnownAs: 2405685:Y6JYY6Q6

COL in the Commonwealth: Sierra Leone - Commonwealth of Learning (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:I3SFDGVA

How can Sierra Leone’s education response after Ebola help with the COVID-19 response? - Bangay, Colin (The Education and Development Forum (UKFIET), 2020)
This blog is written by Colin Bangay, Senior Education Adviser, Department for International Development (DFID). It aims to look at some practical and sensible lessons from the education response in Sierra Leone during the Ebola outbreak, to help others as they face closures of education systems. This blog was originally published on the Global Partnership […]
KerkoCite.ItemAlsoKnownAs: 2339240:D5Q8A77B 2405685:PK7UUFGK

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (World Bank; OECD; Harvard Global Education Innovation Initiative; HundrED, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:BRFU9F86 2405685:93KUAPNF 2405685:9APBFG2P 2405685:CXIWGJLQ 2405685:STZ89LHX 2534378:UQINHJH2

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF

About Us | Teaching Service Commission - Sierra Leone - Teaching Service Commission (Government of Sierra Leone, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:46QDPXDM 2405685:E9YPU485

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Education Sector Analysis: Assessing the enabling environment for gender equality - Republic of Sierra Leone; UNICEF; IIEP-UNESCO Dakar (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3EEMJ5QE 2405685:YIC6SIQI

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707872 2405685:9EPB5ZXS
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Education in Africa: What Are We Learning? - Evans, David; Acosta, Amina Mendez (2020)
Countries across Africa continue to face major challenges in education. In this review, we examine 145 recent empirical studies (from 2014 onward) on how to increase access to and improve the quality of education across the continent, specifically examining how these studies update previous research findings. We find that 64 percent of the studies evaluate government implemented programs, 36 percent include detailed cost analysis, and 35 percent evaluate multiple treatment arms. We identify several areas where new studies provide rigorous evidence on topics that do not figure prominently in earlier evidence syntheses. New evidence shows promising impacts of structured pedagogy interventions (which typically provide a variety of inputs, such as lesson plans and training for teachers together with new materials for students) and of mother tongue instruction interventions, as well as from a range of teacher programs, including both remunerative (pay-for-performance of various designs) and non-remunerative (coaching and certain types of training) programs. School feeding delivers gains in both access and learning. New studies also show long-term positive impacts of eliminating school fees for primary school and positive impacts of eliminating fees in secondary school. Education technology interventions have decidedly mixed impacts, as do school grant programs and programs providing individual learning inputs (e.g., uniforms or textbooks).
KerkoCite.ItemAlsoKnownAs: 2339240:I9QLRLND 2405685:BUVF2SY4
Keywords: ⛔ No DOI found

DSTI Education Data Hub - DSTI (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:IYNCGEPI 2405685:88RPBVJU

Education Innovation Challenge - Reflection & Learning Summit Report - DSTI (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:M28U3MQY 2405685:YNNFWZLA

Sierra Leone Free Education Project - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:MSP6V8I2 2405685:REKP5PJD

Education Workforce Management in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:28FQ3DS8 2405685:QEWLRFDX

Sierra Leone Education Attendance Monitoring System - Teaching Service Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:CLIEEVEU 2405685:XV88ZYD7

Country-level research review: Sierra Leone - Kallon Kelly, Christiana; Koomar, Saalim; Kreimeia, Adam; McBurnie, Chris; Mitchell, Joel; Myers, Christina (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:746WTJF3 2405685:HNVAP5QB
Keywords: dode_eth-src-eth

Teacher Management Policy for Sierra Leone - Teaching Service Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:ILC2GGZX 2129771:XQMFH5JU 2339240:5QZ2N3GQ 2339240:QSY3I4ZA 2405685:M6F97ARN 2405685:RFT2PNDX 4556019:49UIZ3SU
Keywords: _C:Sierra Leone SLE

Education Workforce Spatial Analysis in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:XF3I7T7Y 2339240:Q42KZNBD 2339240:V7GZZAMR 2405685:2HRVB9KF 2405685:4AGUYJZJ 2405685:B5LNLGZL 2405685:FS263PV6 4042040:ZQNXW7RV 4556019:S386467K
Keywords: _yl:a; ⛔ No DOI found

SALCAB | Home - SALCAB (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:7LEIDSTB

Education Workforce Recruitment and Matching in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Workforce Initiative, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:2JR2FXVK 2339240:8YVNU64V 2405685:KZBP674C 2405685:Q8T7NH3C 2405685:S38LF89P 2486141:BQG3BPG7 4556019:S8AD6237
Keywords: _yl:b; ⛔ No DOI found

Education Workforce Supply and Needs in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (the Education Commission; Fab Inc., 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2KB28MDX 2339240:LYKK26AE 2405685:52ZGRDGR 2405685:8MIWRFD2 2405685:QMGGDQ4G
Keywords: ⛔ No DOI found

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:XVKVLR6R 2405685:QV99MR4Q

Systems-Level Analysis of Education Service Delivery in Sierra Leone - Education Partnerships Group (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:8354FEB6 2486141:PFQ2N79R

Innovative Education Workforce Analysis for More Equitable Education: Sierra Leone - Education Workforce Initiative (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:XCXZB356 2405685:67AH3BDQ

Independent Reporting Mechanism (IRM): Sierra Leone Design Report 2019–2021 - Field, Tracey-Lynn (Open Government Partnership, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:8XF8TYGA 2405685:YMJMKLLJ

Sierra Leone Education Attendance Monitoring System (SLEAMS) Final Technical Report - Graham, Hannah; Kawa, Muniru; Lee, Philip; Malyon, Stephanie; Hayward, Harry; Conteh, Sheriff; Chandia, Gloria (Charlie Goldsmiths Associates, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:M68LGCE7 2405685:FTT9TD2Y

Sierra Leone Education Attendance Monitoring System (SLEAMS) Pilot Phase: Inception Report - Kawa, Muniru; Graham, Hannah; Lee, Philip; Murray, Tobias; Malyon, Stephanie (Charlie Goldsmiths Associates, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:EPHMUJLL 2405685:F8XG7GDF

Incidence of HIV, all (per 1,000 uninfected population) - Sierra Leone | Data - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:RSRU6YLV 2405685:RFVHGC9Z 4556019:CI8YJ5UC

Republic of Sierra Leone: Education sector analysis: assessing the enabling environment for gender equality - UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:A6RXK3ZC 2405685:UG524M3N

Education continuity during the Coronavirus crisis: Sierra Leone and Liberia Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Rising Academy Network, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:YUCXSRDK 2405685:U7GMEU2U

Cost Effective Approaches to Improve Global Learning What Does Recent Evidence Tell Us Are Smart Buys for Improving Learning in Low-and-Middle-Income Countries - Global Education Evidence Advisory Panel (World Bank; FCDO; Building Evidence in Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:IL3G2LER 2339240:IQT7LI8P 2405685:9YMXHH74 2405685:CN86U6UQ 2405685:LX2STYUZ

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Effectiveness of Multimodal Microlearning for In-Service Teacher Training - Allela, Melisa Achoko; Ogange, Betty Obura; Junaid, Muhammad Ibn; Charles, Prince Brainard (Journal of Learning for Development, 2020)
To meet the growing demand for continuing professional development of practising teachers, the integrated in-service teacher training (INSET) programme aims at making permanent improvements on the quality of teaching and learning for Junior Secondary School (JSS) Teachers in Sierra Leone. Within this context, a toolkit for School-Based Teacher Development was created and microlearning identified as an ideal mode to deliver the toolkit content. In this paper, we present the design considerations that informed this decision as well as challenges and lessons learned from the first implementation of the INSET project for junior secondary school teachers in Sierra Leone. A multimodal approach was considered and implemented to mitigate Internet access challenges and to expand learning opportunities. These include a mobile app version of the Toolkit, offline access to microlearning resources on the TeacherFutures platform via the Moodle mobile app, a mobile app version of one INSET module, an e-portfolio to be used by participants in sharing their learnings as demonstrated and practised during a face-to-face roll-out seminar, and finally, WhatsApp groups in which different schools engaged in discussions based on the questions on the Toolkit. Preliminary findings indicate a strong preference among participants for the use of WhatsApp as the main channel of communication within the communities of practice; and very limited use of the main e-learning Moodle platform and e-Portfolio. This necessitates a need to critically evaluate the effectiveness of the design of a multimodal approach for delivering microlearning content. From this, we seek to establish a set of design considerations, capacity building and technical support issues derived from analysis of data emerging from the ongoing project rollout. This will inform future integration of Microlearning resources in the teacher training project.
Publisher: Commonwealth of Learning KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v7i3.387 2339240:98GSBC3X 2405685:Z794TZUM
Keywords: Barriers; Communities of Practice; Electronic Learning; Foreign Countries; Inservice Teacher Education; Integrated Learning Systems; Internet; Multimedia Materials; Portfolios (Background Materials); Professional Continuing Education; Professional Development; Program Effectiveness; Secondary School Teachers; Social Media; Synchronous Communication; Teacher Collaboration; Teacher Competencies; Workshops

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
previousshortDOI: 10/ghgng5 previousDOI: 10.5281/zenodo.3762228 EdTechHub.Copy: 2129771:QQWNSYJR EdTechHub.Copy: 2129771:QQWNSYJR shortDOI: 10/ghgng5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3762228 10.53832/edtechhub.0022 10/ghgng5 2129771:QQWNSYJR 2339240:45F2G56T 2405685:3MKIMX34 2405685:A3T2DQ4D 2405685:WB97BS9V
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
ZenodoArchiveID: 4706059 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706059 2339240:3HJRFVNR 2339240:3VR6UC7F 2339240:9U79NYYD 2339240:NCZSLKX5 2339240:UEWQXHSF 2339240:YFCV9UXA 2339240:YMYNESML 2405685:9NJI87R8 2405685:B54L7JGC 2405685:C6QUC3Z7 2405685:D9SU8CEK 2405685:LK4JMG78 2405685:PW66MNDR 2405685:SLJSKY8J 2405685:VSAZQYD7 2405685:Z3XYMJZN
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749654 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749654 2405685:39XPD5EM 2405685:QZ2FJC4E
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode